2015
DOI: 10.1007/s11523-015-0392-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of PD-L1 Expression in Renal Cell Carcinoma. A Systematic Review and Meta-Analysis

Abstract: This meta-analysis indicates that a higher level of PD-L1 expression is a negative prognostic factor in RCC. Its validation as an independent prognostic factor compared to other traditionally used clinical parameters in localized or advanced disease is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 32 publications
2
112
1
Order By: Relevance
“…If this axis is of functional relevance, one might assume that PD1/PD-L1 expression is negatively associated with outcome or with parameters of severe prognosis. In fact, several studies identified such association, at least in ovarian cancer, breast cancer, melanoma, lung cancer as well as in sarcoma [19,[28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this axis is of functional relevance, one might assume that PD1/PD-L1 expression is negatively associated with outcome or with parameters of severe prognosis. In fact, several studies identified such association, at least in ovarian cancer, breast cancer, melanoma, lung cancer as well as in sarcoma [19,[28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, while PD-1 expression frequently was analyzed, the knowledge about PD-L1 expression as well as its prognostic impact in RCC is still limited and in part contradictory [15][16][17][18][19][20]. To further elucidate the pattern of PD-L1 expression in ccRCC, as well as to understand its prognostic impact, we analyzed intratumoral PD-L1 expression in a retrospective cohort of ccRCC specimens.…”
Section: Introductionmentioning
confidence: 99%
“…31 In another meta-analysis of RCC, high level of PD-L1 expression was a negative prognostic factor that increased the risk of death by 81% (hazard ratio, 1.81; 95% CI, 1.31-2.49; P , .001). 33 In gastric carcinoma, PD-L1 expression by immunohistochemistry was associated with larger tumor size, invasion into the deep muscular layers, lymph node metastasis, and decreased survival time of patients (,2 years). 34 Moreover, multivariate analysis demonstrated that PD-L1 immunodetection could be used as an independent factor to evaluate the prognosis of gastric carcinoma.…”
Section: Pd-1/pd-l1 Expression As a Prognostic Marker In Various Cancersmentioning
confidence: 92%
“…However, a few studies revealed that expression of PD-L1 in tumor cells may imply better prognosis. Additionally, several studies beyond those noted in Table 1 showed that PD-L1 expression in tumor cells and tumor-infiltrating lymphocytes is correlated with poor prognosis in such cancers as NSCLC, 31 melanoma, 32 RCC, 33 and esophageal and gastric cancers. 34 A meta-analysis conducted by Wang et al 31 in 1157 patients with NSCLC showed that PD-L1 expression was significantly associated with poor differentiation of tumors (poor versus well: odds ratio, 1.91; 95% CI, 1.33-2.75; P ¼ .001) and with worse overall survival (pooled hazard ratio, 1.75; 95% CI, 1.40-2.20; P , .001).…”
Section: Pd-1/pd-l1 Expression As a Prognostic Marker In Various Cancersmentioning
confidence: 98%
“…Among the first studies in patients undergoing nephrectomy, expression of PD-L1 was associated with a hazard ratio (HR) of 4.5 (95% confidence interval (CI) 1.94-10.56; p < 0.001) for death [18]. More recently, a meta-analysis of 6 studies revealed that PD-L1 expression is found in 24% of clear cell RCC and in only 11% of non-clear cell RCC specimens (p = 0.002) [19]. High PD-L1 expression levels were associated with risk of death (HR 1.81; 95% CI 1.31-2.49; p < 0.001), and this impact on prognosis was maintained in patients with metastatic disease.…”
Section: The Prognostic Role Of Checkpoints In Rccmentioning
confidence: 99%